2-Iodoxybenzoic Acid–Dimethyl Sulfoxide (IBX-DMSO)-Promoted Oxidative Aromatization of Spiro[2.5]octa-4,7-dien-6-one - Li, Tong; Cui, Chaoxing; Zhang, Yuxia; Song, Xixi; Wang, Zechao; Chang, Junbiao (Synlett, 2022)
A 2-iodoxybenzoic acid (IBX)–dimethyl sulfoxide (IBX-DMSO)-promoted oxidative aromatization of spiro[2.5]octa-4,7-dien-6-ones has been developed. A series of substrates with various substitutions were transformed into oxidative aromatization products in good to excellent yields. This oxidative aromatization features environmentally friendly reagents, high efficiency, a broad substrate scope, broad functional-group tolerance, and mild reaction conditions.
Keywords: metal-free reaction; iodoxybenzoic acid; dimethyl sulfoxide; oxidation; aromatization; spirooctadienones